2021
DOI: 10.1097/md.0000000000027247
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of blood leptin and adropin levels in patients with multiple sclerosis

Abstract: Background: The effects of adipokines have been investigated in multiple sclerosis (MS) in the literature. Results are uncertain, and subgroups like adropin have not been previously studied. We primarily aimed to determine leptin and adropin levels in MS and their potential use as a biomarker. Methods: This study was an experimental research. While 44 MS patients diagnosed according to McDonald criteria were included in the patient group, 40 people without MS diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(109 reference statements)
0
1
0
Order By: Relevance
“…[ 10 ] In another study, the rate of HPL in the patient group, was found to be not statistically significant. [ 11 ] In our study, the HPL rate in the patient group was also statistically insignificant compared with the control group.…”
Section: Discussionmentioning
confidence: 44%
“…[ 10 ] In another study, the rate of HPL in the patient group, was found to be not statistically significant. [ 11 ] In our study, the HPL rate in the patient group was also statistically insignificant compared with the control group.…”
Section: Discussionmentioning
confidence: 44%